Analisis Wacana Kritis Berita Pemberian Gelar Guru Besar Kehormatan Kepada Megawati Soekarnoputri - Harun, Arpani (Program Studi Magister Linguistik Terapan UNJ, 2023)
The media, both print and online, not only function as a conveyer of information, but also become a forum for framing certain intentions or ideologies. This framing can be seen through critical reading by identifying the diction, the structure of news content, and the context of news discourse. The aim of this paper was to examine the news related to the issue of awarding an honorary professor title to the former President of the Republic of Indonesia, Megawati Soekarnoputri, in four online media, namely kompas.com, republica.co.id, tribunnews.com and newspapertempo.id. Data collection technique used document. The data was analysed by using the concept of Teun A. Van Dijk’s discourse analysis concept. The results of the analysis show that the four news texts contain of three dimensions text: superstructure, macro structure and micro structure.